2011
DOI: 10.2139/ssrn.1956767
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Level and Uncertainty of Trend Inflation

Abstract: Firmly-anchored inflation expectations are widely viewed as playing a central role in the successful conduct of monetary policy. This paper presents estimates of trend inflation, based on information contained in survey expectations, the term structure of interest rates, and realized inflation rates. My application combines a variety of data sources at the monthly frequency and it can flexibly handle missing data arising from infrequent observations and limited data availability. In order to assess whether inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…For instance, Cogley, et al (2010) investigate autocorrelation in the inflation gap, π t − µ t , and Cecchetti, et al (2007) model log-volatility innovations as a two-state Markov process, thus allowing jumps in r t and q t . Kozicki and Tinsley (2012) and Mertens (2011) introduce survey data on inflation forecasts to aid identification, 16 Mertens (2011) and Stella and Stock (2012) develop multivariate forecasting models by incorporating data on other macroeconomic outcomes such as unemployment and the term structure of interest rates, 17 and Chan, et al (2013) introduce a priori bounds on the random walk component µ t .…”
Section: Price-level Instabilitymentioning
confidence: 99%
“…For instance, Cogley, et al (2010) investigate autocorrelation in the inflation gap, π t − µ t , and Cecchetti, et al (2007) model log-volatility innovations as a two-state Markov process, thus allowing jumps in r t and q t . Kozicki and Tinsley (2012) and Mertens (2011) introduce survey data on inflation forecasts to aid identification, 16 Mertens (2011) and Stella and Stock (2012) develop multivariate forecasting models by incorporating data on other macroeconomic outcomes such as unemployment and the term structure of interest rates, 17 and Chan, et al (2013) introduce a priori bounds on the random walk component µ t .…”
Section: Price-level Instabilitymentioning
confidence: 99%
“…Inflation less trend follows an autoregressive process in some of these studies (e.g., Cogley, Primiceri, and Sargent 2010) but not in others (Stock and Watson 2007). In addition, some research using random walk trends (Stock and Watson 2007, Mertens 2011, and Cogley, Primiceri, and Sargent 2010 has found that the variability of the trend component in inflation has varied over time.…”
Section: Introductionmentioning
confidence: 98%
“…2 A number of studies and still-used forecasting models measure inflation expectations, or in effect, trend inflation, with past inflation (e.g., Brayton, Roberts, and Williams 1999, Gordon 1998, and Macroeconomic Advisers 1997. 3 Another array of studies has modeled trend inflation as following a random walk (e.g., Cogley, Primiceri, and Sargent 2010, Cogley and Sbordone 2008, Ireland 2007, Kiley 2008, Kozicki and Tinsley 2006, Mertens 2011, Piger and Rasche 2008, and Stock and Watson 2007. Inflation less trend follows an autoregressive process in some of these studies (e.g., Cogley, Primiceri, and Sargent 2010) but not in others (Stock and Watson 2007).…”
Section: Introductionmentioning
confidence: 99%
“…2 Modern time series models of the inflation process now routinely embed time-varying volatility and persistence; examples include Stock and Watson (2007), Cogley, Primiceri and Sargent (2010), Mertens (2011), and Clark and Doh (2014). The Markov-switching approach of Nalewaik (2015) does as well, and results here show one advantage of that approach is that a rich set of control variables-labor-market slack, a non-linear function of labor-market slack, the real dollar exchange rate, and bank lending-can be included into the model easily without the imposition of strong prior assumptions.…”
mentioning
confidence: 99%